2017
DOI: 10.1007/s11517-017-1721-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel and reliable computational intelligence system for breast cancer detection

Abstract: Cancer is the second important morbidity and mortality factor among women and the most incident type is breast cancer. This paper suggests a hybrid computational intelligence model based on unsupervised and supervised learning techniques, i.e., self-organizing map (SOM) and complex-valued neural network (CVNN), for reliable detection of breast cancer. The dataset used in this paper consists of 822 patients with five features (patient's breast mass shape, margin, density, patient's age, and Breast Imaging Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Since origin, AI has developed rapidly during the past several decades, and AI-related topics remain hot. We have developed various algorithms to try to put AI into clinical application,59 but we always have been ignoring the patients’ willingness to accept them. In our study, less than half of the participants had ever heard of AIMs (Table 2), which is less than that in the Central and Eastern Europe (CEE) population, according to the first local CEE study on AI conducted for IBM 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since origin, AI has developed rapidly during the past several decades, and AI-related topics remain hot. We have developed various algorithms to try to put AI into clinical application,59 but we always have been ignoring the patients’ willingness to accept them. In our study, less than half of the participants had ever heard of AIMs (Table 2), which is less than that in the Central and Eastern Europe (CEE) population, according to the first local CEE study on AI conducted for IBM 11.…”
Section: Discussionmentioning
confidence: 99%
“…Major disease areas use AI tools include cancer, neurology, and cardiology; mainly, the studies have been about neoplasms 4. For example, Shiraz et al developed a computational intelligence system for breast cancer detection 5. Arau´jo et al demonstrated that they could distinguish breast carcinoma from healthy tissues by histology images using convolutional neural networks (CNNs) with a sensitivity of 95.6% 6.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown in [7] that three-layer neural networks are sufficient for modeling and approximation applications of continuous functions. The number of hidden layer neurons and the type of transfer functions are determined by the type, size, and complexity of the problem.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Artificial neural networks have been widely used in various areas of modeling. For example [6] has discussed different aspects of modeling and analysis of gas turbines operation, and [7] has used neural networks for modeling, controlling and optimization in corrosion phenomenon. In the following, we introduce artificial neural networks briefly and then examine the studied gas pressure boost system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to accurate prediction of the patient's survival, supervised machine learning-based algorithms are also used for classification [35,36] where input values (e.g. an image associated to clinical record) are assigned to an output class (e.g.…”
Section: Introductionmentioning
confidence: 99%